The International Migration of Women - Morrison, Andrew R.; Schiff, Maurice; Sjöblom, Mirja (Washington, DC: World Bank and Palgrave Macmillan, 2012)
Women now account for nearly half of all international migration. Theoretical and empirical models that omit gendered determinants and impacts of migration are missing key elements of the story. Women's roles in destination labor markets and in remittance flows-to cite just two examples-are crucial to understanding the development impacts of international migration. This volume surveys the state of our knowledge and provides new research on the gendered determinants and impacts of migration and remittances as well as on the patterns of labor market participation of women migrants. It also sketches a road map for future research on gender and international migration. This research on women and international migration illustrates the type of analytical work that can shape policies to economically empower women migrants as well as women left behind by male migration. It is authors' hope that such analysis will lead to policies that boost productivity, raise incomes, and improve welfare in both sending and receiving countries. This volume addresses several issues. The introductory chapter provides an overview of the volume; it includes a description of methodology, data, main results, and conclusions from the six remaining chapters. The second chapter reviews the existing research on gender and international migration and can be considered a starting point for the remaining chapters. The third chapter focuses on the gendered determinants of migration and remittances in rural Mexico, an important sending country. The following two chapters (chapters 4 and 5) address the impact of migration and remittances on sending countries and provide analysis of household- level data from Ghana and Mexico. Chapter 6 turns to the labor market participation and performance of female migrants in a major destination country, the United States. The volume concludes with a forward-looking chapter that summarizes the major findings, links those to migration policy, and outlines some of the important research and policy issues that need to be addressed in the future.